Tuning the interface interaction between Nb2O5 nanosheets/graphene for high current rate and long cyclic lithium-ion batteries. (10th December 2022) - Yu, Yanlong; Jin, Yuhang; Hasan, Najmul; Cao, Sufeng; Wang, Xiaoliang; Ming, Hai; Shen, Peixing; Zheng, Runguo; Sun, Hongyu; Ahmad, Mashkoor
Research highlights: The influence of different GO contents on the electrochemical performance of defective Nb2 O5 has been investigated. The improved performance of the electrode owed to the synergy between Nb2 O5 and Go contents. The GO contents increased conductivity and contact area and protects the Nb2O5 matrix from collapse. The oxygen vacancies defects provide more active sites and improve the catalytic activity of the electrode. The lithium storage capabilities of Nb2 O5 structure can be improved by optimizing the GO contents and oxygen vacancies. Abstract: Interface interaction as well as defect-rich nanostructures offer unique opportunity for the fabrication of high-rate performance lithium-ion batteries (LIBs). In this work, adefective multiphase Nb2 O5 -R nanosheets which has interface interaction with graphene oxide (GO) was synthesized. The intensity of interface interaction was tuned by controlling the stoichiometric ratio (Nb2 O5 -R/GO x where x = 1, 5, 10). It is found that Nb2 O5 -R/GO5 electrode exhibits highest reversible capacity at 1 C, 2 C, 5 C, 10 C, 25 C and 35 C, slow capacity retention and a stable columbic efficiency of 93.4%. The electrode demonstrates a reversible capacity of 292.0 mAhg −1 at 1 C after 70 cycles with a capacity retention rate of 89.9% and 220 mAhg −1 is still retained at the rate of 5 C after 800 cycles, which proves its superior cyclic stability. Moreover, the electrochemical impedance spectroscopy (EIS) also confirms the improved kinetics of Nb2 O5 -R/GO5 electrode. The appropriate oxygen vacancies and GO contents, as well as strong interface interaction between Nb2 O5 -R and GO leads to increase in conductivity, structural stability and provide extra active sites for rapid lithium storage.The results provide a new strategy for the development of new anode materials for LIBs with high-rate capability and long cycle life. Graphical abstract: Energy storage performance of Nb2 O5 /GOx nanosheets is investigated. It is found that Nb2 O5 /GO5 structure as anode for lithium-ion battery demonstrates enhanced kinetics, high reversible capacity, good cycling stability and high-rate capability as compare to Nb2 O5, Nb2 O5 -R and Nb2 O5 /GOx electrodes. Image, graphical abstract